Proximate composition and micronutrient profile of different size groups of hilsa Tenualosa ilisha (Hamilton, 1822) from river Ganga - Ganguly, S.; Mahanty, A.; Mitra, T.; Mohanty, B. P. (Indian Journal of Fisheries, 2018)
The Indian shad hilsa, Tenualosa ilisha (Hamilton, 1822) is an important food fish in South-east Asian countries. The fish is rich in oil and known for its high omega-3 polyunsaturated fatty acid (PUFA) content; however information available on the micronutrient profile of this commercially important food fish is limited. The present study investigated the detailed micronutrient profile (mineral and fat soluble vitamins) of different size groups of hilsa. Proximate composition analysis revealed that besides being rich in crude fat (7.91-14.61%), the protein content of this fish is also very high(19.44-21.86%). The macro-minerals potassium, calcium and micro-minerals iron, zinc and the fat soluble vitamins A and E are the dominant micronutrients in different size groups of hilsa. Comparative nutritional evaluation of different size groups of hilsa showed that medium size fish is nutritionally superior to both small and large size groups.